The Impact of Person-Organization Fit Dimensions on Work Performance Case Study: PT. Biofarma (Persero) Indonesia (The Indonesian Journal of Business Administration, 2020)
Over time the pattern of human lifestyle raises the risk of increasing new diseases that are endemic in society. As a preventive way, vaccines are needs to protect human from the disease. One of the companies in Indonesia that produce vaccines and antisera is PT. Biofarma (Persero). The increasing competition in the pharmaceutical industry, especially vaccines, and the decline in revenue has made Biofarma change its corporate culture and corporate value. These cultural and values changes have an impact on the performance decrease of employees and the increasing amount of employees counselling. The impact felt by the employees show that managing human resources is essential to the company to achieve the company’s vision and mission.This study aims to determine whether there is an influence of person-organization fit dimensions on employee performance. The person-organization fit variable refers to the theory of Kristof Brown (1996), which suggests that measurement of person-organization fit can be using two dimensions, namely supplementary fit and complementary fit. The supplementary fit dimension measures the suitability of individual values with company values through the five values applied by Biofarma. The complementary fit dimension measures the fulfilment of employee needs as measured through the hierarchy theory of employee needs from Stum (2001). This study uses a quantitative approach by giving questionnaires to respondents and obtained 460 respondents from various positions and directorates. Data from the questionnaire were processed statistically using SPSS 20. This study uses multiple linear tests and correlations to get the effect between variables. Besides, sub-variables of each variable test using a simple linear test. Based on the results of statistical analysis, found that the two dimensions of person-organization fit influence the performance of employees at PT. Biofarma (Persero). Based on these results, this study provides several recommendations that aim to improve employee performance and will also have an impact on the development and sustainability of the company. Recommendations from this research can be taken into consideration by companies in managing human resources and improving company performance to be able to compete in intense competition in the vaccine industry. Keywords: Person Organization Fit, Work Performance, Company Value, Personal Value, Employee Needs Hierarchy